An honorable man : a novel - Vidich, Paul (Atria Books, 2016)
"This gripping first novel in a spy thriller series, set in Washington D.C. at the height of the Red Scare, investigates a double agent in the CIA whose betrayals threaten to compromise the two lead investigators, the Agency, and the entire nation"--